2019
DOI: 10.1039/c9nj03177d
|View full text |Cite
|
Sign up to set email alerts
|

Complexation of 2-thenoyltrifluoroacetone (HTTA) with trivalent f-cations in an ionic liquid: solvent extraction and spectroscopy studies

Abstract: HTTA forms M(TTA)2+, M(TTA)2+, M(TTA)3° and M(TTA)4− complexes with lanthanides. Complexation is strongly favoured when the salt of TTA− is used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(23 citation statements)
references
References 38 publications
1
21
1
Order By: Relevance
“…The Eu(TTA) 4 − species in RTIL was previously reported 19,32 either in the direct dissolution of Eu(TTA) 3 •H 2 O crystals 32b or in LLE systems. 19,32 Because speciation of the Eu-TTA system in C 4 mim•NTf 2 is well-known, the LLE system species Eu-(TTA) 4…”
Section: Speciation Of Dissolved Eu(iii)mentioning
confidence: 82%
“…The Eu(TTA) 4 − species in RTIL was previously reported 19,32 either in the direct dissolution of Eu(TTA) 3 •H 2 O crystals 32b or in LLE systems. 19,32 Because speciation of the Eu-TTA system in C 4 mim•NTf 2 is well-known, the LLE system species Eu-(TTA) 4…”
Section: Speciation Of Dissolved Eu(iii)mentioning
confidence: 82%
“…For example, while Jensen, et al 29 reported the extraction of anionic species into ionic liquid medium for lanthanides, Okamura, et al 30 reported complete dehydration of the Eu(TTA) 3 (H 2 O) 3 crystal in an ionic liquid. In our earlier work, 31 we reported a detailed investigation on the liquid–liquid extraction and complexation of lanthanides with HTTA in Bumim·Tf 2 N. The liquid–liquid extraction of Eu 3+ performed at pH 3.5 indicated the extraction of anionic species of the type Eu(TTA) 4 − , similar to those reported previously, 29 where the charge balance of the Bumim·Tf 2 N phase was maintained by the transfer of one Tf 2 N − anion into the aqueous phase. The formation of Ln(TTA) 4 − species was subsequently identified by spectrophotometric titration of Nd 3+ with TTA − anions in Bumim·Tf 2 N. However, there is still considerable interest in understanding the speciation of the Ln/TTA complex at varying pH of the aqueous medium.…”
Section: Introductionmentioning
confidence: 88%
“…Detailed methodology for the preparation of Bumim·TTA salt has been described in our earlier communication. 31 At first, HTTA dissolved in hexane was neutralized with ammonia solution at room temperature to obtain a solid product of NH 4 ·TTA. Subsequently, metathesis of NH 4 ·TTA salt with Bumim·Cl in acetone resulted in a water immiscible liquid of Bumim·TTA.…”
Section: Methodsmentioning
confidence: 99%
“…In these cases, metal ions are complexed by the conjugate bases. Among these extractants, numerous studies have been dedicated to the use of the beta-diketone HTTA in imidazolium-based IL ([C 1 C n im] [NTf 2 ]) [114][115][116][117][118] − complexes can be encountered [114]. The stoichiometry of extracted complexes, such as the Ln(TTA) 4 − anionic complex, was confirmed by emission profiles and spectrophotometric titration respectively for Eu 3+ /HTTA and Nd 3+ /HTTA complexes [115].…”
Section: Ionic Exchangersmentioning
confidence: 99%
“…Among these extractants, numerous studies have been dedicated to the use of the beta-diketone HTTA in imidazolium-based IL ([C 1 C n im] [NTf 2 ]) [114][115][116][117][118] − complexes can be encountered [114]. The stoichiometry of extracted complexes, such as the Ln(TTA) 4 − anionic complex, was confirmed by emission profiles and spectrophotometric titration respectively for Eu 3+ /HTTA and Nd 3+ /HTTA complexes [115]. The role of the IL anion with regard to Ln chelates and the extraction mechanism has been evidenced for the bis(trifluoromethanesulfonyl)imide anion (NTf 2 ) [116], as well as nonafluoro-1-butanesulfonate (CF 3 (CF 2 ) 3 SO 3 − ) [117].…”
Section: Ionic Exchangersmentioning
confidence: 99%